Surds and Indices
- If 3x - 3x-1 = 18, then xx is equal to
-
View Hint View Answer Discuss in Forum
∵ 3x - 3x - 1 = 18
⇒ 3x - 1(3 - 1) = 18
Apply the Algebra law,
If aX = aY then X will be equal to Y.
means X = Y;Correct Option: C
∵ 3x - 3x - 1 = 18
⇒ 3x - 1(3 - 1) = 18
⇒ 3x - 1(2) = 18
⇒ 3x - 1 = 18/2
⇒ 3x - 1 = 9
⇒ 3x - 1 = 32
Apply the Algebra law,
If aX = aY then X will be equal to Y.
means X = Y;
⇒ x - 1 = 2
⇒ x = 3
Then xx = (3)3 = 27
- If 2 x - 1 + 2 x + 1 = 320, then find the value of x ?
-
View Hint View Answer Discuss in Forum
∵ 2x - 1 + 2x + 1 = 320
Apply the law of Algebra
⇒ 2x - 1(1 + 2 2 ) = 320
Solve the equation.Correct Option: C
∵ 2x - 1 + 2x + 1 = 320
Apply the law of Algebra
⇒ 2x - 1(1 + 2 2 ) = 320
⇒ 2x - 1(1 + 4 ) = 320
⇒ 2x - 1 x 5 = 320
⇒ 2x - 1 = 64 = 2 x 2 x 2 x 2 x 2 x 2
⇒ 2x - 1 = 26
if pX = pY then X will be equal to Y. means X = Y;
⇒ x - 1 = 6
∴ x = 7
- Value of √5 + 2√6 - 1/√5 - 2√6 is
-
View Hint View Answer Discuss in Forum
√5 + 2√6 - 1/√5 - 2√6
= ((√5 + 2√6 x √5 - 2√6 ) - 1)/√5 - 2√6
Apply the formula of Algebra.
( a + b ) x (a - b ) = a2 - b2Correct Option: B
√5 + 2√6 - 1/√5 - 2√6
= ((√5 + 2√6 x √5 - 2√6 ) - 1)/√5 - 2√6
Apply the formula of Algebra.
( a + b ) x (a - b ) = a2 - b2
= (√(5)2 - (2√6 )2 - 1)/√5 - 2√6
= (√25 - 4 x 6 - 1) /√5 - 2√6
= (√25 - 24 - 1) /√5 - 2√6
= (√ 1 - 1 )/√5 - 2√6
= (1 - 1 )/√5 - 2√6
= 0/√5 - 2√6
= 0
- Find the value of (10)200 ÷ (10)196 .
-
View Hint View Answer Discuss in Forum
Given equation is
(10)200 ÷ (10)196
Apply the law of Algebra
am ÷ an = am ? n
= (10)200 - 196
Correct Option: A
Given equation is
(10)200 ÷ (10)196
Apply the law of Algebra
am ÷ an = am ? n
= (10)200 - 196
= 104
= 10000
- If 2x - 1 + 2x + 1 = 2560, find the value of x.
-
View Hint View Answer Discuss in Forum
2x - 1 + 2x + 1 = 2560
2x - 1 + 2x - 1 + 2 = 2560
Apply the Law of Algebra
Solve the equation.Correct Option: A
2x - 1 + 2x + 1 = 2560
2x - 1 + 2x - 1 + 2 = 2560
Apply the Law of Algebra
2x - 1 + 2x - 1 x 2 2 = 2560
⇒ 2x - 1 ( 1 + 22 ) = 2560
⇒ 2x - 1 = 2560/5 = 512 = 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2
⇒ 2x - 1 = 29
⇒ x - 1 = 9
∴ x = 9 + 1 = 10